The Multiple Metamorphism of Mafic Granulites From the East Hebei Terrane, North China Craton: Insights Into the Transition of Tectonic Regimes - Liu, Ting; Wei, Chunjing; Yang, Chuan; Li, Zhuang (Frontiers in Earth Science, 2022)
The East Hebei terrane from the North China Craton preserves the dome–and–keel structures, which was transected by a later linear belt in the north margin. Mafic granulites from the linear belt and domes record two groups of metamorphic ages at Neoarchean and Paleoproterozoic, but their accurate metamorphic peak conditions as well as paths have not been well addressed. Three samples of mafic granulites, including two-pyroxene granulite (JD15120), garnet-bearing two-pyroxene granulite (YC8-43) and garnet clinopyroxene granulite (JD1546), were documented for detailed metamorphic studies. Two-episode metamorphism can be recognized. The first-episode recovered from JD15120 and YC8-43, is represented by peak assemblage of medium-grained clinopyroxene, orthopyroxene, amphibole, plagioclase and ilmenite, which yields ultra-high temperature (UHT) conditions of 940–960 °C at 7.5–8.5 kbar and 950–990 °C at 8 kbar respectively, constrained by contours of the maximum anorthite (XAn) in plagioclase cores. The post-peak evolution is dominated by cooling with decompression, constrained mostly from the measured core–to–rim decreasing XAn in plagioclase. By contrast, the second-episode overprinting is recognized in all of samples, but exhibits varying textures. In garnet-bearing samples (YC8-43 and JD1546), the overprinting assemblages are characterized by poikilitic garnet that occurs either as coronae around the first-episode pyroxenes, forming “red-eye socket” textures, or as grains in equilibrium with tiny-grained clinopyroxene, plagioclase, amphibole, rutile and quartz, forming high-pressure (HP) granulite assemblages. These HP granulite assemblages show peak conditions of ~12 kbar/860 °C and ~12.6 kbar/835 °C, constrained by contours of the maximum grossular (XGrs) in garnet cores and the minimum XAn in plagioclase cores. The post-peak evolution is dominated by isothermal decompression, constrained from the outwards decreasing XGrs in garnet and increasing XAn in plagioclase. LA-ICP-MS U-Pb zircon dating on JD15120 and JD1546 suggests two metamorphic ages of ~2.49 Ga and ~1.78 Ga, being considered to be correlated with the UHT and HP granulite metamorphism, respectively. Tectonically, the late Neoarchean UHT granulite metamorphism may correlate a vertical sagduction regime, whereas the late Paleoproterozoic HP granulite metamorphism is favored to register the continental collision in the northern margin of the North China Craton. This study may have indications for the Neoarchean-Paleoproterozoic tectonic transition of the craton.